Desain Alat Pemulasaran Jenazah Covid-19 - Oxa Mariana; Hamdan Bahalwan (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
The Covid-19 virus is a Virused that attacks the respiratory system that has symptoms similar to the common cold. Along the time, this virus mutates so that people who have the congenial diseases can be affected. Infection from this virus is so fast that the WHO (World Health Organization) has designated the Covid-19 virus that caused a pandemic on March 11, 2020. This virus that caused a lot of positive victims and fatalities. These fatalities are increasing as the time goes by until hospitals and the other health agencies collapse. The officers need assistive devices to shorten the time for taking care of the bodies. The mortuary tools of Covid-19 are the tools that can assist the officers. This research uses a mixed-method for data collection with qualitative and quantitative approaches. Qualitative data were obtained from interviews and abservations in hospitals, public health care, and mosques, while quantitative data has obtained from literature, journals, and other support data. The analytical methode used is design analysis. The form of the mortuary tool has obtained the result of implementing the needs of the mortuary needs is a mortuary tools that could shorten time of funeral due to the Covid-19 pandemic.